A Ba Speaking to His Owner: Warning about an Imminent Danger and Giving an Admonition - Almansa-Villatoro, M. Victoria.
This paper aims to give an explanation for the anomalous fact that a living man can speak with his Ba within the Egyptian literary text, Dialogue between a Man and His Ba. This research notes that rare conversations between humans and other entities occur in Egyptian literature when a warning or an admonition is given to the main character. It is argued that in this case only the Ba can restrain his suicidal owner from death. doi: http://dx.doi.org/10.5913/jarce.52.2016.a001